Дослідження методів та моделей управління IT-проєктами з розробки комп’ютерних ігор - Дроздов, Я. Д.; Петров, К. Е. (ХНУРЕ, 2025)
This paper examines existing models and methods of IT project management in the field of computer game development. Popular methodologies such as Agile, Scrum and Kanban are analyzed, as well as their application in the game development industry. The main problems and limitations of these approaches are identified. Based on the conducted research, an experimental method of game project management is developed, which takes into account the features of game development and combines elements of existing methodologies. The study proposes the partial probabilistic forecasting as the main method to use.
Keywords: управління IT-проєктами; розробка ігор